Pengaruh Kompetensi SDM dan Ketersediaan Fasilitas Kerja terhadap Kinerja Karyawan Sppg Klasur Kota Sorong - Axel Sianipar; Aprita Manori; Isran Isran; Frans Tipawael; Beatrix Uwaubun (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of human resource competence and the availability of work facilities on employee performance at the Nutrition Fulfillment Service Unit (SPPG) Klasur, Sorong City. The background of this research is the heavy operational workload to produce and distribute 3,200 nutritious food portions daily, handled by only 47 employees consisting of 1 Head of SPPG, 1 Accountant, 1 Nutritionist, 1 Field Assistant, and 43 operational staff. This study utilizes a quantitative approach with a saturated sampling technique (N = 47). Data analysis was performed using multiple linear regression via IBM SPSS Statistics 26. The regression analysis produced the equation Y = 1.974 + 0.173X1 + 0.611X2. The partial test results (t-test) show that HR Competence (X1) has a positive and significant effect on employee performance (t-count 2.241 > t-table 2.015, sig. 0.021), and Work Facilities Availability (X2) has a dominant positive and significant effect (t-count 4.832 > t-table 2.015, sig. 0.000). Simultaneously, the F-test confirms a significant effect (F-count 29.733 > F-table 3.21, sig. 0.000). The coefficient of determination (R Square) is 0.575, implying that 57.5% of employee performance variation is explained by these two variables, while the remaining 42.5% is influenced by factors outside this study.